2017
DOI: 10.1073/pnas.1617533114
|View full text |Cite
|
Sign up to set email alerts
|

Ca 2+ -binding protein 2 inhibits Ca 2+ -channel inactivation in mouse inner hair cells

Abstract: Ca 2+ -binding protein 2 (CaBP2) inhibits the inactivation of heterologously expressed voltage-gated Ca 2+ channels of type 1.3 (Ca V 1.3) and is defective in human autosomal-recessive deafness 93 (DFNB93). Here, we report a newly identified mutation in CABP2 that causes a moderate hearing impairment likely via nonsense-mediated decay of CABP2-mRNA. To study the mechanism of hearing impairment resulting from CABP2 loss of function, we disrupted Cabp2 in mice (Cabp2 LacZ/LacZ ). CaBP2 was expressed by cochlear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
84
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(94 citation statements)
references
References 65 publications
9
84
0
1
Order By: Relevance
“…For example, alternative splicing and RNA editing can produce Ca v 1 channels in neurons with limited CDI (Bazzazi et al, 2013; Shen et al, 2006; Singh et al, 2008; Tan et al, 2011). It is noteworthy that knock-out of CaBP2 causes increased voltage-dependent inactivation rather than CDI of the Ca v 1.3 current in inner hair cells (Picher et al, 2017), despite evidence that CaBP2 strongly suppresses CDI of Ca v 1.3 channels in transfected HEK293T cells (Schrauwen et al, 2012). Clearly, the native environment in which Ca v channels are expressed may strongly influence the extent to which Ca v channels are modulated by CaBPs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, alternative splicing and RNA editing can produce Ca v 1 channels in neurons with limited CDI (Bazzazi et al, 2013; Shen et al, 2006; Singh et al, 2008; Tan et al, 2011). It is noteworthy that knock-out of CaBP2 causes increased voltage-dependent inactivation rather than CDI of the Ca v 1.3 current in inner hair cells (Picher et al, 2017), despite evidence that CaBP2 strongly suppresses CDI of Ca v 1.3 channels in transfected HEK293T cells (Schrauwen et al, 2012). Clearly, the native environment in which Ca v channels are expressed may strongly influence the extent to which Ca v channels are modulated by CaBPs.…”
Section: Discussionmentioning
confidence: 99%
“…Of the multiple CaBP family members, CaBP2 is specifically enriched in inner and outer hair cells (Cui et al, 2007; Yang et al, 2016). However, CDI of Ca v 1.3 in inner hair cells of CaBP2 knock-out mice was not affected (Picher et al, 2017), despite the fact that CaBP2 strongly suppresses CDI of Ca v 1.3 channels in transfected HEK293 cells (Schrauwen et al, 2012). Thus, whether CaBPs regulate CDI of Ca v 1 channels in neuronal cell-types remains to be established.…”
Section: Introductionmentioning
confidence: 99%
“…However, in IHCs, both CDI and VDI are extremely slow. Suppression of CDI is mediated by CaMlike Ca 2+ -binding proteins, such as CaBP2, which are abundantly expressed in IHCs [48,55,69] and inhibit CaMmediated CDI [15,68]. In contrast, the molecular basis for the uniquely slow VDI in IHCs is incompletely understood, although several factors are known to modulate VDI.…”
Section: Introductionmentioning
confidence: 99%
“…Recent work revealed that the number, activation kinetics and open probability of these channels not only differ based on their tonotopic position along the cochlear axis , but also depend on their subcellular AZ localization , thereby suggesting the location‐dependent presence of yet‐to‐be‐identified regulatory proteins. In this context, Ca V 1.3 channels have been shown to be regulated by a number of modulatory proteins, including Gipc3 and CaBP2 (for a recent extensive review on this topic see Ref. ).…”
mentioning
confidence: 99%